2020
DOI: 10.21203/rs.3.rs-69694/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Absence of critical thickness in improper ferroelectric hexagonal-YbFeO3 thin films

Abstract: Improper ferroelectrics are highly promising for technological applications due to their expected persisting polarizations even at ultrathin limits. However, the evolution of their electrical behaviors with thickness, including the magnitude of the polarization and the switching mechanism, remain unresolved experimentally. This is primarily due to the difficulty in growth and characterization of ultrathin improper ferroelectric films. Here, we investigated the spontaneous polarization and switching mechanism i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Xu et al [ 20 ] designed a ferroelectric/dielectric bilayer structure with h-YbFeO 3 as the improper ferroelectric (FE) and CoFe 2 O 4 as the dielectric (DE) with the goal to tune the electrostatic energy of the (FE/DE) bilayer system and to study the electrostatic effect of the DE layer on the spontaneous polarization of the FE layer. Their atomic-resolution cross-sectional scanning transmission electron microscopy (STEM) high-angle annular dark-field (HAADF) imaging demonstrated a periodic arrangement with “two-up-one-down” and “two-down-one-up”, corresponding to the FE polarization [ 20 , 21 , 22 ]. The influence of the film thickness ratio of the FE to DE layers on the ferroelectric polarization has been discussed [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Xu et al [ 20 ] designed a ferroelectric/dielectric bilayer structure with h-YbFeO 3 as the improper ferroelectric (FE) and CoFe 2 O 4 as the dielectric (DE) with the goal to tune the electrostatic energy of the (FE/DE) bilayer system and to study the electrostatic effect of the DE layer on the spontaneous polarization of the FE layer. Their atomic-resolution cross-sectional scanning transmission electron microscopy (STEM) high-angle annular dark-field (HAADF) imaging demonstrated a periodic arrangement with “two-up-one-down” and “two-down-one-up”, corresponding to the FE polarization [ 20 , 21 , 22 ]. The influence of the film thickness ratio of the FE to DE layers on the ferroelectric polarization has been discussed [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Epitaxial growth of rare earth hexaferrite (h-RFeO 3 , R = Y, Dy-Lu) thin films including h-YbFeO 3 have recently attracted the attention of several researchers as it has been successfully stabilized in a metastable hexagonal structure (P63 cm) [ 1 , 2 , 3 ] by depositing it onto substrates with a hexagonal crystal structure like Al 2 O 3 [ 4 , 5 , 6 , 7 ], YSZ(111) [ 6 , 7 , 8 , 9 ], MgO [ 5 ], and substrates buffered with platinum (Pt) [ 4 , 5 , 9 ], Fe 3 O 4 [ 10 ], indium tin oxide (ITO) [ 8 , 9 , 11 ], SrTiO 3 (STO), and others [ 7 , 12 , 13 ]. Jeong et al [ 4 ] demonstrated the ferroelectricity of h-YbFeO 3 films at room temperature (RT) for a film thickness of about 60 nm, where the films were grown by pulsed laser deposition (PLD) on sputtered Pt-buffered sapphire.…”
Section: Introductionmentioning
confidence: 99%
“…There have recently been several attempts to produce h-YbFeO 3 -based devices since the growth of a bottom electrode, such as Pt [ 4 , 5 , 9 ], ITO [ 8 , 9 , 11 ] or La 2/3 Sr 1/3 MnO 3 (LSMO) [ 12 , 13 ], has become crucial for the characterization of ferroelectric and dielectric properties. Moreover, it is worthwhile to highlight the importance of tailoring the interfacial strain either by examining different substrates [ 7 ] or by introducing an underlayer, which could be simultaneously utilized as a bottom electrode.…”
Section: Introductionmentioning
confidence: 99%